The Effect of Job Description Clarity on Employee Performance at Cafe X in Bandung - Azka Qisthiya Putri; Windy Anisa Putri; Gurawan Dayona Ismail; Recky Recky (Indonesian Journal of Innovation Multidisipliner Research, 2026)
The clarity of job descriptions is a crucial factor in the operational efficiency of the Food and Beverage (F&B) industry to minimize role uncertainty and improve staff work effectiveness. This study aims to analyze the effect of job description clarity on employee performance at Café X in Bandung. The research method used is a quantitative approach with an associative design. The study population comprised all 37 employees of Café X, with saturated sampling used as the sampling technique. Data collection was conducted by distributing a structured questionnaire using a Likert scale (1–5) that measured indicators of clarity of tasks, authority, responsibilities, and performance standards (job description), as well as task performance and contextual performance. The data analysis techniques used were simple linear regression, correlation tests, and the coefficient of determination test (R² ) using SPSS. The regression analysis yielded the equation Y = 16.976 + 0.421X. The results of the hypothesis test (t-test) showed a calculated t-value of 3.294 with a significance level of 0.002 (p < 0.05), proving that the clarity of the job description has a positive and significant effect on employee performance. The coefficient of determination (R² ) test yielded a value of 0.237, indicating that the clarity of job descriptions accounts for 23.7% of the variation in employee performance, while the remaining 76.3% is influenced by other variables outside the research model. The implications of this study underscore the importance of management periodically updating and disseminating job descriptions to maintain the quality of the café’s operational services.